Pengembangan Model Desain Pembelajaran untuk Meningkatkan Kecerdasan Majemuk Siswa SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Putri, Khilda Jumhadi; Ilyasa, Nabila (TSAQOFAH, 2023)
Several studies show that students have interests, skills, and intelligence that definitely contribute to their perspective, participation, and performance in academic matters. Students, although different from one another, certainly look for interesting activities and assignments where they can learn lessons and where they can apply their intelligence. Allowing students to choose and work on tasks that interest them and at the same time they can mobilize their intelligence can definitely increase their participation and performance especially for low performing literary genres. Therefore, this research focuses on developing learning designs to improve multiple intelligences. This research uses descriptive research and development methods. The results of the study show that the application of teaching with multiple intelligences allows students at SD Negeri Empang Bahagia 3 Tangerang City to think more critically and have other talents.